2005
DOI: 10.1016/j.cell.2004.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Trimeric G Protein-Dependent Frizzled Signaling in Drosophila

Abstract: Frizzled (Fz) proteins are serpentine receptors that transduce critical cellular signals during development. Serpentine receptors usually signal to downstream effectors through an associated trimeric G protein complex. However, clear evidence for the role of trimeric G protein complexes for the Fz family of receptors has hitherto been lacking. Here, we show roles for the Galpha(o) subunit (Go) in mediating the two distinct pathways transduced by Fz receptors in Drosophila: the Wnt and planar polarity pathways.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
289
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 255 publications
(315 citation statements)
references
References 47 publications
(4 reference statements)
21
289
1
1
Order By: Relevance
“…Inhibition of G ao affected the interaction of Axin2 and GSK3 but not the interaction of Axin and GSK3, whereas inhibition of G aq had the opposite effect . As G-proteins function downstream of Frizzled (Liu et al, 2001b;Katanaev et al, 2005), this result indicates that two parallel pathways mediated by different G proteins differentially regulate Axin and Axin2. However, it is still not clear why GSK3 dissociates from Axin in response to Wnt signaling in 3T3-L1 cells, whereas it remains bound in L929 cells.…”
Section: B-cateninmentioning
confidence: 94%
“…Inhibition of G ao affected the interaction of Axin2 and GSK3 but not the interaction of Axin and GSK3, whereas inhibition of G aq had the opposite effect . As G-proteins function downstream of Frizzled (Liu et al, 2001b;Katanaev et al, 2005), this result indicates that two parallel pathways mediated by different G proteins differentially regulate Axin and Axin2. However, it is still not clear why GSK3 dissociates from Axin in response to Wnt signaling in 3T3-L1 cells, whereas it remains bound in L929 cells.…”
Section: B-cateninmentioning
confidence: 94%
“…WTX, which is vertebrate specific, thus has dichotomic roles in Wnt signaling, analogous to those for Axin and GSK3. The FZD topology invites GPCR comparisons, and FZD coupling to trimeric G-proteins in Wnt/b-catenin signaling has received certain support from pharmacological and genetic studies (Ahumada et al 2002;Katanaev et al 2005;Liu et al 2005;Schulte and Bryja 2007), although this remains a debated issue. Although Gao and Gaq are suggested to regulate Axin-GSK3 interaction (Liu et al 2005), Gbg is shown to be in complex with LRP6, DVL, and Axin and to recruit GSK3 to phosphorylate LRP6 (Jernigan et al 2010).…”
Section: Lrp6 Phosphorylation: Roles Of Pip2 G-protein and Other Kimentioning
confidence: 99%
“…One possibility is through Fz-mediated G protein signaling. Studies in both mammalian cell culture and Drosophila (Katanaev et al 2005) suggest Gao is required for Wnt/bcat signaling. This requirement is upstream of Dvl (Katanaev et al 2005), suggesting a model in which information is passed from Fz to Gao to Dvl (Fig.…”
Section: Pip5kmentioning
confidence: 99%